Reluctant transformers: The institutional logics of German savings banks climate finance - Ulrich Klüh; Ilias Naji (Hochschule Darmstadt, Fachbereich Wirtschaft, Zentrum für Nachhaltige Wirtschafts- und Unternehmenspolitik ZNWU, 2025)
What defines the role of public savings banks("Sparkassen") in tackling the socio-ecological challenges related to planetary boundaries, such as climate change and loss of biodiversity? A clear answer to this question is still lacking, in spite of that fact that the German Sparkassen have recently become more ambitious with respect to their role in the sustainability transformation. Taking these recent developments into account, we provide a qualitative empirical analysis of the institutional logics that shape the savings banks' response to repeated calls to deepen their involvement in ecological sustainability efforts. We argue that the lack of transformative potential that many observers have criticized is due to a specific combination of institutional logics, that emphasize compliance, competitiveness and controlling activities. Moreover, savings banks appear to be following a strategy of conservative transformation, consistent with the approaches they have followed in recent decades, to survive in a climate hostile to public ownership of financial institutions and relationship banking. We observe tendencies to make climate finance a vehicle to become relationship-orientated again, and identify the obstacles standing in the way of such a twist.
Keywords: B15; B25; B26; B52; E02; E58; N2; 330; Savings Banks; Climate Finance; Sustainability; Institutional Logics; Financialization